Managing Investment Risks: Modern V/s Traditional Knowledge and Practices - Swami, Rakesh; Kumar Jain, Trilok (Journal of Advanced Research in HR and Organizational Management, 2023)
The present study is a comparative study between modern investment tools and old investment tools. The study has been conducted in Rajasthan (India) and therefore the old tools of investment available in Rajasthan have been identified and compared with the modern tools. The primary purpose of the study was to compare the risk management tools available a common investor. The researchers found that the traditional tools or the old tools were also very good, but the modern tools offer more systematic and secure options. The researchers conclude that the modern tools are better in comparison to the traditional tools.